Outcome-Based Education (OBE) Curriculum: MBKM's Impact on Employability Skills in Arabic Education Graduates at Jambi University - Muhammad Sobri; Zainul Mustofa, Ady Muh.; Yusup , Agung; Abdullah, Nurazzelena Binti (Universitas Islam Negeri Jurai Siwo Lampung, 2025)
This study examines the implementation of the Outcome-Based Education (OBE) curriculum under the Merdeka Belajar-Kampus Merdeka (MBKM) policy and its role in enhancing employability skills in the Arabic Language Education program at Jambi University. Addressing the gap between labor market demands and conventional curriculum limitations, the research employed a qualitative case study approach, collecting data through interviews (5 lecturers, 5 students), participant observation (Teaching Campus activities, collaborative projects), as well as document analysis (MBKM policies, syllabi). Findings indicate that OBE-MBKM integration improves graduate employability, with internships, industry projects, and student exchanges fostering practical, communication, and leadership skills. Institutional support (lecturer training, industry networks) is key, yet challenges persist, including uneven lecturer understanding, infrastructure gaps, and weak industry partnerships. The study affirms the potential of OBE-MBKM potential to boost graduate competitiveness but highlights the need for systematic improvements in lecturer capacity, facilities, and stakeholder collaboration. Theoretically, it contributes to employability skill integration in higher education; practically, it offers policymakers actionable insights for designing market-responsive curricula.